Tunnelling behaviour of the Asian subterranean termite in heterogeneous soils: presence of cues in the foraging area - Lima, Juliana Toledo [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2012)
Exploitation of the environment by building a tunnel network is one of the stages involved in the foraging behaviour of subterranean termites, and it may be influenced by several factors, such as temperature, soil, drought, floods, predators, competitors, obstacles or even a lack of food. Because soils in natural environments are generally very heterogeneous, our aim in the present study was to analyse the tunnelling behaviour of the Asian species Coptotermes gestroi in the presence of physical, chemical and biological cues in the substrate (twisted wire, a pre-existing tunnel and a tunnel containing three dead soldiers of Heterotermes tenuis or C. gestroi) in bidimensional glass arenas. All experiments were run in Biochemical Oxygen Demand incubator (25 +/- 0.2 degrees C), and the arenas were digitally photographed after 24 h. Fewer primary tunnels were constructed in the absence of guidelines (control treatments) than in the presence of guidelines (experimental treatments), demonstrating more vigorous initial tunnelling behaviour in the presence of guidelines in the soil. In addition, termites in experimental treatments either clearly followed the solid guideline in several regions of the tunnelling arena, or spread their network of tunnels from the preformed excavation, and their tunnelling patterns differed from those of the controls. Finally, foragers usually avoided contact with dead soldiers by constructing primary tunnels at different sites from those where dead soldiers had been placed. These results indicate that behavioural patterns of C. gestroi foragers are altered when tunnelling substrates are not homogeneous. (C) 2012 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.
Keywords: Coptotermes gestroi; defence behaviour; food search; foraging; guideline; Isoptera; passageway; Rhinotermitidae; termite; tunnelling behaviour